Nasjonal identitet, det overnaturlige og oversettelsesstrategier - Lange, Tadeusz Wojciech (Versita, 2012)
The article discusses translation strategies used by the author when dealing with culture-specific references/concepts in the rendition in Polish of the Norwegian fantasy trilogy The Sign of the Elves by Sigbjørn Mostue. The challenge here lay in that the novels feature a number of characters inspired by Norwegian folklore. Of the following translation strategies that in the author’s opinion are possible, but not as yet fully listed anywhere, i.e. 1) direct borrowing 2) literal translation 3) direct borrowing + footnote 4) literal translation + footnote 5) direct borrowing + descriptive explanation 6) literal translation + descriptive explanation 7) substitution with another reference from source culture 8) substitution with another reference from target culture 9) substitution with another reference from universal/global culture 10) substitution with translator’s own coinage 11) evasion by simplification 12) evasion by omission, strategies 1, 2, 5, 8, 9, 10 and 11 were used in the translation in question. In his choice of the (mostly functional) equivalents in the target language, the translator drew upon two main sources: Slavic demonology and role-playing games (RPGs).
National Identity, the Supernatural and Translation Strategies
Keywords: Oversettelsesstrategier; Kulturspesifikke referanser; Det overnaturlige; Vette; Eventyrverden; Fantasi; Folkeminne; Translation strategies; Culture-specific references; The supernatural; Fabulous; Fantasy; Folklore